Соціологічний підхід до розуміння права в спадщині Станіслава Дністрянського - Олещук, Катерина Михайлівна; Олещук, Екатерина Михайловна; Oleshchuk, Kateryna M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Досліджено соціальні підстави права в уявленні С. Дністрянського. За визначенням науковця право є соціальним явищем, адже народжується в соціальних зв’язках як потреба організації суспільного порядку. В основу права вчений закладає морально-етичні компоненти, які виникли природно й діють у вигляді звичаєвого права в соціальних зв’язках. Їм (морально-етичним компонентам) науковець надає пріоритетного значення, порівняно з нормативними складниками. Research of S. Dnistryansky scientific heritage is the result of the revival and continuation of traditions of research that laid the foundations of modern sociology of law and legal thinking in Ukraine. The main objective of Dnistryansky is: - focus on the sociological basis of inheritance S. Dnistryansky. To his mind the right is a product of social interaction, because there is only where are social connection which are subject to economic objectives. Social connection are a source of law, because it comes from the families, genera, states on the one hand, and social organizations on the other hand; - Find out the basics principles of social order and forms of law in society. Scientist defined value that it belongs to the fundamentals of law that is the cause of law-making, and what are social forms of interaction, in which the law is manifested, that is the result.-Identify the social meaning of the concept and essence of law in the teaching of scientist. Providing significant weight to state apparatus, made the moral law as a component in determining when compared with normative.
Sociological Approach to Understanding the Law in the Works of Stanislav Dnistryanskу
Keywords: соціологічне праворозуміння; соціальні основи права; форми права; звичаєве право; соціальна етика; закон; державне право; sociological thinking; social foundations of law; forms of law; customary law; social ethics; law; state law